Investigating consumer acceptance of smart speaker commerce: insights from a broad mass survey - Münch, Christopher (29th EurOMA Conference, 2022)
Smart speakers are expected to be an important sales channel. However, since there is no research on what factors drive consumers to use such speakers, this study examines these acceptance factors by creating and testing a technology acceptance model by conducting a survey. The collected data were then analyzed using structural equation modeling. The results confirm that perceived usefulness and customer experience directly influence consumers' intention to use smart speaker commerce. In contrast, system quality and personal level of innovation have little indirect influence on consumer intention. Perceived risk has no statistically significant influence on smart speaker commerce adoption.